Compressive Strength Properties of Natural Gas Hydrate Pellet by Continuous Extrusion from a Twin-Roll System - Yun-Hoo Lee; Bong-Hwan Koh; Heung Soo Kim; Myung Ho Song (Advances in Materials Science and Engineering)
This study investigates the compressive strength of natural gas hydrate (NGH) pellet strip extruded from die holes of a twin-roll press for continuous pelletizing (TPCP). The lab-scale TPCP was newly developed, where NGH powder was continuously fed and extruded into strip-type pellet between twin rolls. The system was specifically designed for future expansion towards mass production of solid form NGH. It is shown that the compressive strength of NGH pellet strip heavily depends on parameters in the extrusion process, such as feeding pressure, pressure ratio, and rotational speed. The mechanism of TPCP, along with the compressive strength and density of pellets, is discussed in terms of its feasibility for producing NGH pellets in the future.